Knowledge of Students Regarding COVID-19 Amid its Hasty Expansion - Manisha Saklani; Parvinder Kaur; Jyoti Sarin (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background: The pandemic of COVID-19 has been spreading around the world very rapidly and has took aterrible shape. The one of the better ways to deal with this terrible pandemic is to have thorough knowledgeabout it and act consequently.Objectives: The present study aim at assessing and comparing the knowledge of Students about COVID 19and its hasty expansion.Material and Methods: Descriptive cross-sectional research design was adopted for the study. Data usingonline structured knowledge questionnaire was collected from 316 participants which was selected usingconvenient sampling technique from selected University of Ambala. The data was collected from studentsof Nursing, Physiotherapy and IT department.Results: The mean age of participants among Nursing was 21.75 + 1.77, 23.43 + 2.62 among physiotherapywhereas 23.22+ 2.28 among IT department. In relations to Gender it was found that most (76 %) of theparticipants were female and only 24 percent were male among Nursing, 66 percent’s participants werefemale, and 34 percent were male among physiotherapy while 56 percent were female and 44 percentwere male in the IT department. 47 percent participants from the Nursing, 40 percent participants fromphysiotherapy and 20 percent participants form IT were having good knowledge. The knowledge scoreamong Nursing Participants ranged from 17 to 46, 15 to 47 among Physiotherapy whereas it was 17 to 47among IT participants. The mean knowledge score of the Nursing participants was 33.84 + 5. 48, 32.91+6.67among physiotherapy and it was 31.63+5.98 among IT. Repeated measure ANOVA was calculated whichshows a statically significant difference (F=1.07, p=0.00) among three groupsConclusion: The study concluded that continuing teaching experience is required to the students regardingpreventive measures as well as change in the treatment regimen